2015
DOI: 10.1007/s40843-015-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Confined growth of CdSe quantum dots in colloidal mesoporous silica for multifunctional nanostructures

Abstract: We report a new and convenient strategy for incorporating fluorescent semiconductor nanocrystals into silica hosts for the synthesis of multifunctional nanostructures. Mesoscale porosity was first created in conventional Stöber silica spheres by chemical etching under the protection of polymeric ligands. Uniform and highly luminescent CdSe nanocrystals were then directly grown in the porous silica network by reacting the silica spheres in a growth solution at high temperature. The confinement of silica network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[59][60][61][62][63] QDs have been explored to prepare barcodes for bio-detection, cell labelling, imaging, anti-counterfeiting and other applications by putting them in/on nanospheres, nanoclusters, nanosheets, nanorods, nanotubes, nanowires and nanodisks. 33,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] 2.1.1.3 Fluorescent carbon dot encoded nano-barcodes. Fluorescent carbon dots (CDs) are small carbon nanoparticles of size less than 10 nm.…”
Section: Optical Encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61][62][63] QDs have been explored to prepare barcodes for bio-detection, cell labelling, imaging, anti-counterfeiting and other applications by putting them in/on nanospheres, nanoclusters, nanosheets, nanorods, nanotubes, nanowires and nanodisks. 33,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] 2.1.1.3 Fluorescent carbon dot encoded nano-barcodes. Fluorescent carbon dots (CDs) are small carbon nanoparticles of size less than 10 nm.…”
Section: Optical Encodingmentioning
confidence: 99%
“…Using this process, CdSe QD precursors are embedded and grown directly under high temperature conditions inside porous silica nanospheres to prepare the barcode element. 64 The swelling method is advantageous due to its applicability to a wide range of organic and inorganic dyes and nanoparticles to prepare nano-as well as micro-barcodes. 36,175,176 The successful embedding using this approach, however, requires a match between the pore size of the nanospheres and the size of the encoding element.…”
Section: Embeddingmentioning
confidence: 99%
“…The pH value of the solution was adjusted to 10 using 1 M NaOH. A fresh NaHSe solution was rapidly injected into the above solution under a nitrogen stream, and stirred vigorously for 30 min, and the mixture was refluxed at 60 °C for 2 h, thereby obtaining bright yellow CdSe quantum dots [28,29].…”
Section: Synthesis Of Cdse Quantum Dotsmentioning
confidence: 99%
“…, enhance the chemical stability of the QDs [26,27], and promote surface conjugation with the ligand [15]. Moreover, it was reported that a silica shell can prolong the shelf life of QD devices: after long-term operation for 100 h at a driving current of 60 mA, a silica QD-LED retained 88% of its initial QY, while a pristine QD-LED only retained 65% of its initial value [28].…”
Section: +mentioning
confidence: 99%